Staggered reinforced Al-Mg-Si alloy and preparation method thereof

Through high-energy ball milling and powder rolling deformation technology, the layered reinforced Al-Mg-Si alloy is formed, which solves the problem that the strength and plasticity of traditional Al-Mg-Si alloys are difficult to match, and the combination of high strength and excellent plasticity is achieved, and the combination of high strength and excellent plasticity is achieved. Its application scope.

CN119307763AInactive Publication Date: 2025-01-14YANTAI ADVANCED MATERIALS & GREEN MFG SHANDONG PROVINCIAL LAB +1

Patent Information

Application Number
CN202411848268.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

While increasing strength, traditional Al-Mg-Si alloys reduce plasticity, resulting in material brittleness, limiting their application range.

Method used

After high-energy ball milling and cold pressing molding, it is placed in a stainless steel sleeve for preheating and insulation and multi-pass powder rolling deformation to form a layered-match reinforced Al-Mg-Si alloy, which is improved by nano-scale layered-match and twin structure. Material properties.

Benefits of technology

Al-Mg-Si alloy has excellent plasticity while maintaining high strength, with a yield strength of 390~670 MPa, a tensile strength of 500~700 MPa, a density of more than 99.5%, and an elongation of 3.5~7%. , broaden the application areas of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307763A_ABST
    Figure CN119307763A_ABST
Patent Text Reader

Abstract

The invention relates to a fault strengthening type Al-Mg-Si alloy and a preparation method thereof.The preparation method comprises the following steps that after a process control agent and aluminum alloy powder are subjected to high-energy ball milling, cold press forming is conducted, and a preformed blank is obtained; the obtained prefabricated blank is placed in a stainless steel sleeve for preheating and heat preservation; and carrying out rolling deformation on the pre-heated and heat-preserved prefabricated blank and the stainless steel sleeve to obtain the fault strengthening type Al-Mg-Si alloy. After the aluminum alloy powder is subjected to high-energy ball milling, cold press molding and powder rolling deformation, the obtained Al-Mg-Si alloy is good in strength, and the density and plasticity are obviously improved. The preparation method is simple, the compactness is good, and the application field of the Al-Mg-Si alloy is effectively expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metals, and in particular relates to a stacking fault strengthened Al-Mg-Si alloy and a preparation method thereof. Background Art

[0002] Al-Mg-Si alloy has the characteristics of low density, good corrosion resistance and excellent processing performance. It is widely used in aerospace, rail transportation, building materials and other fields, and has good application prospects. However, the strength and plasticity of traditional Al-Mg-Si alloys are often low, making it one of the obstacles to its widespread application. In order to improve the strength of Al-Mg-Si alloys, existing research generally improves the mechanical properties of materials by adding metal or non-metal elements. With the addition of metal or non-metal elements, while Al-Mg-Si alloy materials gain high strength, their plasticity gradually decreases, showing a certain brittleness. This conflict between strong and plastic is difficult to match, but it prevents further improvement of strength and limits the scope of application of Al-Mg-Si alloys.

[0003] The strengthening mechanism of traditional aluminum alloy materials includes fine grain strengthening, solid solution strengthening, second phase strengthening and dislocation strengthening, etc. The increase in strength is obtained by the precipitation phase hindering the movement of dislocations. Therefore, while obtaining high strength, cracks are introduced to cause brittle fracture of the material and reduce plasticity, which greatly limits the application range of aluminum alloy plates. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and propose a method for preparing a stacking fault strengthened Al-Mg-Si alloy, which can effectively achieve that the Al-Mg-Si alloy has excellent plasticity while maintaining high strength.

[0005] The present invention provides a method for preparing a stacking fault strengthened Al-Mg-Si alloy, comprising the following steps: Step 1: subjecting the process control agent and aluminum alloy powder to high-energy ball milling and then cold pressing to obtain a preform; the aluminum alloy powder comprises the following components by mass fraction: 1-6% Mg; 0.1-1.2% Si; the remainder is Al; Step 2: Place the preform obtained in step 1 in a stainless steel sleeve and preheat at 500-640°C; Step 3: rolling and deforming the preform and the stainless steel sleeve preheated and heat-insulated in step 2 to obtain a stacking fault-strengthened Al-Mg-Si alloy.

[0006] Furthermore, the process control agent in step 1 is at least one of anhydrous ethanol, acetone, n-hexane, polyethylene glycol and kerosene, more preferably at least one of anhydrous ethanol, acetone and polyethylene glycol, and most preferably anhydrous ethanol or polyethylene glycol. The polyethylene glycol is preferably a high molecular weight polyethylene glycol, and the molecular weight of the polyethylene glycol is preferably 10000-18000, more preferably 12000-15000.

[0007] Furthermore, the time of the high energy ball milling in step 1 is 20 to 60 h, preferably 30 to 50 h, and most preferably 40 to 48 h; the ball to material ratio of the high energy ball milling is (10 to 15):1, preferably (11 to 13):1, and most preferably 12:1.

[0008] Furthermore, the addition amount of the process control agent and the aluminum alloy powder in step 1 is: the addition amount of the process control agent per 1 kg of aluminum alloy powder is 10-20 mL.

[0009] Furthermore, the cold pressing pressure in step 1 is 30-40 MPa.

[0010] Furthermore, the stainless steel sleeve in step 2 is one of 304 stainless steel, 316 stainless steel and 430 stainless steel. The stainless steel sleeve assists deformation and prevents cracking of the blank.

[0011] Furthermore, the preheating and heat preservation time in step 2 is 10 to 60 minutes, preferably 20 to 40 minutes, and more preferably 30 minutes.

[0012] Furthermore, the preheating and heat preservation temperature in step 2 is 550-620°C, preferably 580-620°C.

[0013] Furthermore, the rolling deformation in step 3 is a multi-pass rolling, and the pressing amount of each rolling is 0.05~0.5mm, preferably 0.15 mm; during each rolling deformation process, the forging is placed in a high-temperature furnace at 560~620℃ for supplementary heating, and each pass is kept warm for 3~10min, preferably 4~8min, and most preferably 5min; the total deformation is 20~80%, preferably 30~80%, and most preferably 70%.

[0014] The present invention also provides a stacking fault strengthened Al-Mg-Si alloy, and the Al-Mg-Si alloy is prepared by the above preparation method.

[0015] Furthermore, the Al-Mg-Si alloy has a yield strength of 390-670 MPa, a tensile strength of 500-700 MPa, a density of more than 99.5%, and an elongation of 3.5-7%.

[0016] Compared with the prior art, this application has at least the following beneficial effects:

[0017] In this application, after high-energy ball milling, cold pressing and powder rolling deformation of aluminum alloy powder, the Al-Mg-Si alloy obtained has good strength, a yield strength of 390~670 MPa, and a tensile strength of 500~700 MPa. In addition, the density (density reaches more than 99.5%) and plasticity (elongation is 3.5~7%) are also significantly improved. The preparation method of the present invention is simple and has good density, which effectively opens up the application field of Al-Mg-Si alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a metallographic optical micrograph of the Al-Mg-Si alloy obtained in Example 1 of the present invention; Figure 2 This is a metallographic optical micrograph of the Al-Mg-Si alloy obtained in Example 2 of the present invention; Figure 3 This is a metallographic optical micrograph of the Al-Mg-Si alloy obtained in Example 3 of the present invention; Figure 4 This is a metallographic optical micrograph of the Al-Mg-Si alloy obtained in Example 4 of the present invention; Figure 5 This is a metallographic optical micrograph of the Al-Mg-Si alloy obtained in Example 5 of the present invention; Figure 6 This is a transmission electron microscopic morphology image of the Al-Mg-Si alloy obtained in Example 3 of the present invention. DETAILED DESCRIPTION

[0019] The present invention discloses a novel stacking fault strengthened Al-Mg-Si alloy and a preparation method thereof. Those skilled in the art can refer to the contents of this article and implement it by appropriately changing the process parameters. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The embodiments described below are only descriptions of the preferred embodiments of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the scope of protection determined by the claims of the present invention.

[0020] The aluminum alloy powder described in the present invention is prepared into a powder block through high-energy ball milling and cold pressing, and the powder block is placed in a stainless steel sleeve, which is then kept warm at high temperature and then powder rolled to finally prepare a high-strength stacking fault-reinforced Al-Mg-Si alloy plate. The present invention introduces a large number of nano-scale stacking faults and twins during high-energy ball milling. On the basis of grain refinement, the alloy plate performance is strengthened by a large number of nano-scale stacking faults and twin structures. There is no need to perform a solution aging heat treatment process, and finally a high-strength Al-Mg-Si alloy plate is obtained. No atmosphere protection is required during the preparation process, and the process flow is suitable for modern industrial equipment, which effectively broadens the application field of Al-Mg-Si alloy plates. The present invention is further described below in conjunction with the embodiments:

[0021] Example 1

[0022] 5000 g of aluminum alloy powder (Al-1Mg-0.4Si) was put into a ball mill with a ball-to-material ratio of 12:1. The process control agent was 40 mL of anhydrous ethanol. After high-energy ball milling for 60 h, it was cold pressed at a pressure of 40 MPa to obtain a preform. The prepared preform was placed in a 304 stainless steel sleeve. After being kept at 600℃ for 30 min, the preform and the stainless steel sleeve were powder rolled. The rolling deformation process was carried out on a double-roll rolling mill with multiple rolling deformation passes. During each rolling deformation process, the forging was placed in a high-temperature furnace at 600℃ for supplementary heating. The temperature was kept for 6 min during each pass. The pressing amount for each pass was 0.15 mm. The final deformation of the alloy reached 40%, and then it was air-cooled to room temperature to finally obtain a stacking fault-strengthened Al-Mg-Si alloy.

[0023] Example 2

[0024] 5000 g aluminum alloy powder (Al-2Mg-0.8Si) was put into a ball mill with a ball-to-material ratio of 12:1. The process control agent was 20 mL of anhydrous ethanol and 100 g of polyethylene glycol. After high-energy ball milling for 45 h, the preform was cold pressed at a pressure of 35 MPa to obtain a preform. The obtained preform was placed in a 316 stainless steel sleeve. After being kept at 620℃ for 40 min, the preform and the stainless steel sleeve were powder rolled. The rolling deformation process was carried out on a double-roll rolling mill with multiple rolling deformation passes. During each rolling deformation process, the forging was placed in a high-temperature furnace at 620℃ for supplementary heating. The temperature was kept for 8 min during each pass. The pressing amount for each pass was 0.20 mm. The final deformation of the alloy reached 60%, and then it was air-cooled to room temperature to finally obtain a stacking fault-strengthened Al-Mg-Si alloy.

[0025] Example 3

[0026] 5000 g aluminum alloy powder (Al-3Mg-0.6Si) was put into a ball mill with a ball-to-material ratio of 10:1 and a process control agent of 150 g polyethylene glycol. After high-energy ball milling for 48 h, it was cold pressed at a pressure of 40 MPa to obtain a preform. The obtained preform was placed in a 316 stainless steel sleeve, and after being kept at 600℃ for 30 min, the preform and the stainless steel sleeve were powder rolled. The rolling deformation process was carried out on a double-roll rolling mill with multiple rolling deformation passes. During each rolling deformation process, the forging was placed in a high-temperature furnace at 600℃ for supplementary heating. The temperature was kept for 5 min during each pass, and the pressing amount for each pass was 0.20 mm. The final deformation of the alloy reached 60%, and then it was air-cooled to room temperature to finally obtain a stacking fault-strengthened Al-Mg-Si alloy.

[0027] Example 4

[0028] 5000 g of aluminum alloy powder (Al-4Mg-0.4Si) was put into a ball mill with a ball-to-material ratio of 12:1 and 60 mL of anhydrous ethanol as the process control agent. After high-energy ball milling for 46 h, the preform was cold pressed at a pressure of 40 MPa to obtain a preform. The obtained preform was placed in a 430 stainless steel sleeve and kept at 620℃ for 30 min. The preform and the stainless steel sleeve were powder rolled. The rolling deformation process was carried out on a double-roll mill with multiple rolling deformations. During each rolling deformation process, the forging was placed in a high-temperature furnace at 620℃ for supplementary heating. The temperature was kept for 6 min during each pass. The pressing amount for each pass was 0.20 mm. The final deformation of the alloy reached 40%, and then it was air-cooled to room temperature to finally obtain a stacking fault-strengthened Al-Mg-Si alloy.

[0029] Example 5

[0030] 5000 g aluminum alloy powder (Al-4Mg-0.8Si) was put into a ball mill with a ball-to-material ratio of 15:1. The process control agents were 20 mL of anhydrous ethanol and 50 g of polyethylene glycol. After high-energy ball milling for 40 h, the preform was cold pressed at a pressure of 35 MPa to obtain a preform. The obtained preform was placed in a 430 stainless steel sleeve and kept at 560℃ for 30 min. The preform and the stainless steel sleeve were powder rolled. The rolling deformation process was carried out on a double-roll mill with multiple rolling deformations. During each rolling deformation, the forging was placed in a high-temperature furnace at 560℃ for supplementary heating. The temperature was kept for 6 min during each pass. The pressing amount for each pass was 0.20 mm. The final deformation of the alloy reached 50%, and then it was air-cooled to room temperature to finally obtain a stacking fault-strengthened Al-Mg-Si alloy.

[0031] The high-strength Al-Mg-Si alloys obtained in Examples 1 to 5 have good compactness and good interface bonding with the matrix. The Al-Mg-Si alloys obtained in Examples 1 to 5 were subjected to metallographic microstructure tests. The test diagram is shown in FIG. Figures 1 to 5 .in, Figure 1 This is a metallographic optical micrograph of the Al-Mg-Si alloy prepared in Example 1; Figure 2 This is a metallographic optical micrograph of the Al-Mg-Si alloy prepared in Example 2; Figure 3 This is a metallographic optical micrograph of the Al-Mg-Si alloy prepared in Example 3; Figure 4 This is a metallographic optical micrograph of the Al-Mg-Si alloy prepared in Example 4; Figure 5 This is a metallographic optical micrograph of the Al-Mg-Si alloy obtained in Example 5; Figure 6 The transmission electron micrograph of the Al-Mg-Si alloy prepared in Example 3. Figures 1 to 5 It can be seen that the Al-Mg-Si alloys prepared in Examples 1 to 5 of the present invention have uniform microstructure distribution, a small amount of elemental Si, and almost no cracks or holes. Figure 6 It can be seen that there are a large number of stacking faults in the matrix.

[0032] The Al-Mg-Si alloys prepared in Examples 1 to 5 of the present invention were sampled, polished, and tested. The tensile test was conducted in accordance with GB / T228.1-2010 "Metallic Material Tensile Test Part 1: Room Temperature Test Method". During the test, at least three tensile specimens were prepared for the samples prepared in the examples to ensure the accuracy and repeatability of the test data. Examples 1 to 5 of the present invention were all measured using an Instron tensile testing machine. During the whole process of the test, a video extensometer was used to monitor the tensile displacement of the specimens. The tensile rate was 0.5 mm / min. The Al-Mg-Si alloy properties obtained by the test are shown in Table 1. Table 1 also contains a comparative example, which is a 6061 aluminum alloy sheet (GB / T 3880.2-2012).

[0033] Table 1 Performance test results of Examples 1 to 5 and Comparative Example 1

[0034] It can be seen from Table 1 that the stacking fault-strengthened Al-Mg-Si alloy forgings and plates prepared in the present invention have excellent mechanical properties, a tensile strength of 500-700 MPa, and an elongation of 3.5-7%. For example, the yield strength of the Al-Mg-Si alloy plate of Example 3 reaches 635.8 MPa, the tensile strength reaches 670.9 MPa, and the elongation reaches 6.63%.

[0035] As an excellent structure, stacking fault can improve the strength of materials without sacrificing plasticity. However, the stacking fault energy of Al is 122-144mJ / m 2 , which is much greater than the energy required for dislocation movement. Therefore, it must be subjected to high stress induction or reasonable composition control. Therefore, how to induce high-density stacking faults in aluminum alloys is the current difficulty in the preparation of Al-Mg-Si alloys. Generally speaking, due to the high stacking fault energy of the aluminum lattice, it is difficult to produce stacking faults in aluminum and aluminum alloys. However, based on the theory of dislocation emission from grain boundaries as Frank-Reed dislocation sources, as the grain size decreases, compared with full dislocations, the critical shear stress required for incomplete dislocations decreases, the tendency of grain boundaries to emit incomplete dislocations increases, and the tendency of grain boundaries to emit full dislocations decreases. The high strength of the Al-Mg-Si alloys obtained in Examples 1 to 5 of the present invention comes from the synergistic effect of fine grains, internal dislocations, and stacking faults contained in the matrix.

[0036] The present invention utilizes high-energy ball milling technology, and by regulating the ball milling process and process control agent, ultrafine, high-performance aluminum alloy powder can be obtained, laying a good foundation for subsequent powder rolling molding. The ultrafine aluminum alloy powder is obtained, that is, the grain refinement is due to the large plastic deformation that occurs during the ball milling process, and the grains are refined to 300-800nm.

[0037] In the process of high-energy ball milling, the present invention refines the grains, thereby increasing the emission tendency of partial dislocations. At the same time, the impact of the steel ball provides large mechanical deformation and shear stress, which, when coupled, lead to stacking faults in the aluminum powder, and the stacking faults meet and merge to produce micro twins. Since the partial dislocations constituting the extended dislocations are Shockley partial dislocations, they cannot climb at high temperatures, so they are relatively resistant to high temperatures, and can be retained in the powder rolling molding stage, becoming an effective strengthening structure of the Al-Mg-Si aluminum alloy material.

[0038] During the high-energy ball milling process, cold welding and fracture repeatedly occur between aluminum alloy powders to form fine particles. The anhydrous ethanol added during the ball milling process is wrapped on the surface of the aluminum alloy powder as an anti-forging agent, which plays a role in preventing the powder from being oxidized and maintaining the surface activity of the powder. Then, a hydraulic press is used to cold-press the powder to obtain a uniform blank with a density of about 70%. On this basis, the ethanol atmosphere wrapped on the surface of the small particles is released by preheating the blank, and then an ultra-fine, highly active surface is exposed. The powder particles with high activity on the surface are quickly sintered by a powder rolling process under pressure, thereby achieving effective bonding between particles, and the defects and holes in the powder blank are eliminated by a reasonable powder rolling deformation process to obtain a high-strength Al-Mg-Si alloy sheet, and the obtained sheet microstructure is fine and uniform, and finally a high-strength aluminum alloy sheet is obtained, and the present invention is carried out under air atmosphere throughout the process.

[0039] The present invention has important significance and role in broadening the application scope of Al-Mg-Si alloy sheet. The present invention can be summarized in other specific forms that do not violate the spirit or main features of the present invention. Therefore, no matter from which point of view, the above embodiments of the present invention can only be regarded as an explanation of the present invention and cannot limit the present invention. The claims indicate the scope of the present invention, while the above description does not indicate the scope of the present invention. Therefore, any changes within the meaning and scope equivalent to the claims of the present invention should be considered to be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a stacking fault strengthened Al-Mg-Si alloy, characterized in that: The following steps are involved: Step 1: subjecting the process control agent and aluminum alloy powder to high-energy ball milling and then cold pressing to obtain a preform; the aluminum alloy powder comprises the following components by mass fraction: 1-6% Mg; 0.1-1.2% Si; the remainder is Al; Step 2: Place the preform obtained in step 1 in a stainless steel sleeve and preheat at 500-640°C; Step 3: rolling and deforming the preform and the stainless steel sleeve preheated and heat-insulated in step 2 to obtain a stacking fault-strengthened Al-Mg-Si alloy.

2. The method for preparing the stacking fault strengthened Al-Mg-Si alloy according to claim 1, characterized in that: The process control agent in step 1 is at least one of anhydrous ethanol, acetone, n-hexane, polyethylene glycol and kerosene.

3. The method for preparing the stacking fault strengthened Al-Mg-Si alloy according to claim 1, characterized in that: The time of high energy ball milling in step 1 is 20-60 h, and the ball-to-material ratio of high energy ball milling is (10-15):

1.

4. The method for preparing the stacking fault strengthened Al-Mg-Si alloy according to claim 1, characterized in that: The addition amount of the process control agent and the aluminum alloy powder in step 1 is: the addition amount of the process control agent per 1 kg of aluminum alloy powder is 10-20 mL.

5. The method for preparing the stacking fault strengthened Al-Mg-Si alloy according to claim 1, characterized in that: The cold pressing pressure in step 1 is 30-40 MPa.

6. The method for preparing the stacking fault strengthened Al-Mg-Si alloy according to claim 1, characterized in that: The preheating time in step 2 is 10-60 minutes, and the temperature is 550-620°C.

7. The method for preparing the stacking fault strengthened Al-Mg-Si alloy according to claim 1, characterized in that: The rolling deformation in step 3 is a multi-pass rolling, and the pressing amount of each rolling is 0.05~0.5 mm; during each rolling deformation process, the forging is placed in a high-temperature furnace at 560~620℃ for supplementary heating, and the heat preservation is 3~10min between each pass; the total deformation is 20~80%.

8. A stacking fault strengthened Al-Mg-Si alloy, characterized in that: The Al-Mg-Si alloy is prepared by the preparation method according to any one of claims 1 to 8.

9. The stacking fault strengthened Al-Mg-Si alloy according to claim 8, characterized in that: The Al-Mg-Si alloy has a yield strength of 390-670 MPa, a tensile strength of 500-700 MPa, a density of more than 99.5%, and an elongation of 3.5-7%.

Citation Information

Patent Citations

  • Squeeze casting forming method for Al-Si aluminum alloy elements

    CN109746415A

  • Preparation method of nano-phase reinforced aluminum-based composite board

    CN111451514A

  • Preparation method of high-strength aluminum alloy forge piece

    CN116334427A

  • High-strength high-plasticity pure aluminum material and preparation method thereof

    CN117380949A

  • High-strength and high-plasticity aluminum alloy and preparation method thereof

    CN117505833A

Cited By

  • A high-strength, high-conductivity, heat-resistant rare-earth aluminum alloy overhead conductor for achieving capacity expansion without tower replacement and its preparation method.

    CN122677248A